UV Light Induced Thermoluminescence of Rare Earth doped Nanomaterials Y\(_2\)O\(_3\):Eu\(^3+\), Gd\(_2\)O\(_3\):Eu\(^3+\) and Gd\(_2\)O\(_3\):Er\(^3+\) - Hai, Nguyen Thi Quy; Anh, Tran Kim; Ha, Vu Thi Thai; Chau, Pham Thi Minh; Tuyen, Ho Van; Thanh, Nguyen Trong; Minh, Le Quoc (Communications in Physics, 2018)
Thermoluminescence properties of ultraviolet irradiated Y2O3:Eu3+, Gd2O3:Eu3+ and Gd2O3:Er3+ nanophosphors have been reported. The materials were synthesized by gel- combustion method with EDTA- Na2 as organic agent. This method allows production of very fine white powder at low temperature with very high efficiency. XRD has been studied to determine the structure of the prepared nano powders. The obtained materials exhibit sufficient sensibility to UV radiation and may be useful in UV light measurements.